Belle and Sebastian [videorecording (DVD)]. - Karvo, Tcheky; Bossuet, Félix, 2005-; Aubry, Cécile (Omnibus Entertainment, 2015)
It all happened way up in the Alps, where the snow is pristine, where chamois and marmots frolic, where soaring peaks scrape the clouds. A solitary little boy meets a stray dog, and so begins a story of enduring friendship. The timeless tale tells the story of how Sebastian tamed Belle; the extraordinary adventures of a resourceful, adorable boy during the Second World War.